Measuring academic research: how to undertake a bibliometric study - Andrés, Ana (Chandos [u.a.], 2009)
Many analyses have been applied in relation to bibliometric studies, but few have shown how to actually carry out the analysis. This book shows how to undertake a bibliometric study, providing a guide from the first step in which the study has to be set, to the analysis and interpretation